Issues Associated with the Use of Untreated Roadside Springs as a Source of Drinking Water. (29th January 2016) - Swistock, Bryan; Clark, James; Boser, Susan; Oleson, Diane; Galford, Amy; Micsky, Gary; Madden, Mark
Abstract: Roadside springs are prevalent across Pennsylvania, but little information has been available about their public use or their suitability as a drinking water source. Penn State Extension conducted research to document roadside spring use and drinking water quality between 2013 and 2015. A survey of over 1, 000 Pennsylvania residents found that 30% have consumed water from a roadside spring and 12% consume water every year, mostly because they perceive the water as natural with a good taste. A synoptic survey of 37 springs in 2013–2014 found that more than 90% failed one or more health‐based drinking water standards. A more intensive follow‐up study in 2014–2015 on ten of the 37 roadside springs found that they consistently failed drinking water standards throughout the year, including some presence of both Giardia and Cryptosporidium cysts. Total coliform bacteria were found to be a better indicator of the overall microbiological drinking water safety of these springs than Escherichia coli bacteria when only a single sample is collected. The frequent use of roadside springs along with poor drinking water quality represent a significant health risk that needs to be addressed in public health education programs.